1994
DOI: 10.1530/jrf.0.1000005
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate receptor gene expression in the hamster hypothalamus and in immortalized luteinizing hormone-releasing hormone neurones

Abstract: Although the excitatory amino acid (EAA) receptor agonist N-methyl-D-aspartate (NMDA) can exert profound stimulatory effects on the neuroendocrine reproductive axis of Syrian hamsters, the exact relationship between NMDA receptors and LHRH neurones is unclear. In the present study, in situ hybridization histochemistry was performed on sections of hamster brain using an 35S-labelled riboprobe to the EAA receptor gene, NMDAR1. A high content of NMDA receptor mRNA was detected not only in brain areas classically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Functional studies also support the absence or extremely low expression of ionotropic glutamate receptors in GT1-7 cells, as GT1-7 cells were shown to be resistant to glutamate toxicity, and patch-clamp studies revealed that NMDA was unable to induce currents in GT1-7 cells. Native GnRH neurons have also been reported to be resistant to glutamate toxicity [47], which agrees with no or low expression of ionotropic glutamate receptors in native GnRH neurons [17, 18, 19, 20]. Likewise, Seeburg and Spergel [personal commun.]…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Functional studies also support the absence or extremely low expression of ionotropic glutamate receptors in GT1-7 cells, as GT1-7 cells were shown to be resistant to glutamate toxicity, and patch-clamp studies revealed that NMDA was unable to induce currents in GT1-7 cells. Native GnRH neurons have also been reported to be resistant to glutamate toxicity [47], which agrees with no or low expression of ionotropic glutamate receptors in native GnRH neurons [17, 18, 19, 20]. Likewise, Seeburg and Spergel [personal commun.]…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, there is abundant evidence that glutamate acts through an indirect mechanism to stimulate GnRH secretion. For instance, the aforementioned lack or low expression of NMDAR1 mRNA in GnRH neurons in male hamsters and male and female rats argues for an indirect mechanism of action [17, 18, 19, 20]. In agreement with a lack or low expression of glutamate ionotropic receptors in GnRH neurons in vivo, Ebling et al [47]recently reported that NMDA and kainate injected into the cortical area, striatum and preoptic area caused massive neuronal loss, but GnRH neurons were spared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggests that EAA receptors may in fact be present on GnRH neurons and that EAAs may regulate GnRH release directly. Along these lines, Urbanski et al [96] have reported that the immortalized GT1-7 GnRH neurons grown in culture contain high levels of NMDA receptor mRNA. This is at variance with the in vivo findings described earlier where less than 5% of GnRH neurons possessed NMDA recep tor mRNA [93], Clearly, more work is necessary to resolve this issue.…”
Section: Eaa Effect -Direct or Indirect On Gnrh Neurons?mentioning
confidence: 99%